Characteristics of children and adolescents presenting to the emergency department with self-inflicted injury: Retrospective analysis of two teaching hospitals - Tu-Hsuan Chang; Chun-Hsien Yu; Giou-Teng Yiang; Han-Yun Chang; Jun Yi Sim (Elsevier, 2022)
Background: Data on Taiwanese adolescents with self-inflicted injuries are limited. We describe the epidemiology of children and adolescents visiting the emergency department for self-inflicted injuries in two geographically distinct teaching hospitals. Methods: Medical records of children 0-18 years old who visited the emergency department of Taipei Tzu Chi Hospital and Chi Mei Medical Center, Tainan between 2016 and 2019 coded with relevant diagnoses were reviewed. Visits with documented self-inflicted injury were included. Results: During the 4-year period, 62 children made 74 emergency visits for self-inflicted injury. A total of 88% of visits were made by children with a psychiatric diagnosis, with depressive disorders being the most common (57%). Interpersonal relationship issue was cited as a trigger for self-harm in 49% of visits. Adjusted for annual visit volumes, self-harm visits per 10,000 pediatric emergency visits increased nearly 5 fold between 2016 and 2019, with the most prominent increase in the final year. Poisoning was the most common mechanism of injury and was frequently used by females, as compared to males who tended to jump from heights. Up to 96% of adolescents with previous self-harm seen at the emergency department had sought psychiatric help in the past year. Urban-rural inequity in mental health resource utilization was observed. Conclusions: Visits to the emergency department for self-inflicted injuries among children and adolescents increased, most remarkably in 2019, for both hospitals. Intentional poisoning with prescription and over-the-counter medications was the most common method. There was a high prevalence of psychiatric disorders in our study population. As the emergency department is likely the first point of medical contact for such visits, emergency personnel should be trained appropriately on managing such patients.